The Effect of Accounting Conservatism on Share Liquidity in Joint Stock Companies Listed on the Palestine Stock Exchange and the Amman Stock Exchange - Majd abu hijleh (An-Najah National University, 2025)
This study aims to verify accounting conservatism affects the liquidity of shares of companies that are listed on the Amman and Palestine stock exchanges. From 2009 to 2022, 202 businesses listed on the Amman Stock Exchange and the Palestine Stock Exchange were included in this study's annual panel data (cross-sectional/time series). Multiple linear regression, the method of moments (GMM) model, and descriptive statistics were employed. to evaluate the research hypothesis. And Because they were newly listed, we did not include companies like Al-Safa Bank Company, Arkan Real Estate Company, Ibn Sina Specialized Hospital Company, and Amlak Real Estate Investment and Trade Company that were listed on the Palestine Stock Exchange because we did not have annual reports for them for all of the study's years. to reach the Palestine Stock Exchange's total number of listed businesses (45). The findings show that during the study period, accounting conservatism had a positive impact on stock liquidity, that when accounting conservative measures increase, stock liquidity increases as well. The findings of the investigation reported in the study contribute to the body of knowledge that is both theoretical and practical. It fills up the pertinent gap. The effect of accounting conservatism on stock liquidity.
أثر التحفظ المحاسبي على سيولة الأسهم في الشركات المساهمة العامة المدرجة في بورصة فلسطين وبورصة عمان